Fabrication and Photosensitivity of CdS/Silicon Nanoscrew Photoresistor. Issue 27 (22nd September 2017) - Liu, Jing; Yi, Futing; Zhou, Yue; Wang, Bo; Zhang, Tianchong; Wang, Yuting
Abstract: Silicon nanoscrews with aspect ratio of 3, 6 and 9 corresponding to 4, 8 and 12 etching cycles are fabricated by CsCl self‐assembly lithography and inductively coupled plasma (ICP) dry etching with "Bosch Process", which can reduce the reflection to below to 10% for wavelength from 400 to 1000 nm. A layer of Cadmium sulfide (CdS) film covers onto the silicon nanoscrews surface to photoresistor. The XRD pattern shows the CdS packed both on the nanoscrew and planar surface are well‐crystallized. The nanoscrew substrate with the large surface ratio can increase the light absorption and quantity of sensitive material, which can improve the photosensitivity of the CdS photoresistor compared to the planar one obviously. However, the aspect ratio of nanoscrew is not the larger the better for that the high aspect ratio also increases the difficulty of CdS package. The photosensitivity response test results show that the nanoscrew photoresistor with 6 aspect ratio has the best performance under different illumination. With 10000 μW/cm 2, the best photosensitivity response achieves to 141 for nanoscrew sample. Abstract : Silicon nanoscrews with aspect ratio of 3, 6 and 9 corresponding to 4, 8 and 12 etching cycles are fabricated. A layer of Cadmium sulfide film covers onto the silicon nanoscrews surface to photoresistor. The photosensitivity response test results show that the nanoscrew photoresistor with 6 aspect ratio has the best performance under different illumination. With 10000 μW/cm 2, the best photosensitivity response achieves to 141 for nanoscrew sample.